Rent control and rental prices: High expectations, high effectiveness? - Philipp Breidenbach; Lea Eilers; Jan Ludwig Fries (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2019)
This paper evaluates the rent control policy implemented in Germany in 2015. Like many countries around the world, German cities and metropolitan areas have experienced a strong increase in rental prices during the last decade. In response, the politicians aimed to dampen the rise in rental prices by limiting the landlords' freedom to increase rents for new contracts. To that end, the rent control was introduced. To evaluate the effectiveness of the rent control with respect to rental prices, we take advantage of its restricted scope of application. First, it is applied only in a selected number of municipalities, thereby generating regional variation. Second, the condition of rental objects generates an additional dimension of variation since new and modernised objects are exempt from rent control. Based on data for rental offers in Germany, we apply a triple-differences framework with region-specific time trends as well as flat type-specific ones. Despite the high political expectations, our estimates indicate that the German rent control dampens rental price growth by only 2.5 %. This effect varies across object characteristics and seems to be larger for lower-quality, smaller-sized dwellings and in the lower price segment. Nevertheless, the application of an event-study indicates that these effects are not persistent over time.
Keywords: C23; R31; 330; rental prices; rent control; regional variation; regulation; diff-in-diff-in-diff; event study